2006
DOI: 10.1007/s10495-006-8764-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of caspase-dependent mitochondrial permeability transition protects airway epithelial cells against mustard-induced apoptosis

Abstract: In the present study, the toxicity of yperite, SM, and its structural analogue mechlorethamine, HN2, was investigated in a human bronchial epithelial cell line 16HBE. Cell detachment was initiated by caspase-2 activation, down-regulation of Bcl-2 and loss of mitochondrial membrane potential. Only in detached cells, mustards induced apoptosis associated with increase in p53 expression, Bax activation, decrease in Bcl-2 expression, opening of the mitochondrial permeability transition pore, release of cytochrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 58 publications
5
24
1
Order By: Relevance
“…Surprisingly, our data showed no evidence that broad caspase inhibition after SM exposure had any effect on AChE activity or the percentage of TUNEL positive cells. The apparent discrepancies between our data and a previous report where zVAD showed marked protection against SM-induced apoptosis in 16HBEo − -cells (Sourdeval et al, 2006) may be due to the use of a different cell lines or due to differences in study design. In our protocol cells were not pre-treated or co-incubated with the inhibitor during SM exposure to avoid direct interaction of SM with zVAD.…”
Section: Discussioncontrasting
confidence: 99%
“…Surprisingly, our data showed no evidence that broad caspase inhibition after SM exposure had any effect on AChE activity or the percentage of TUNEL positive cells. The apparent discrepancies between our data and a previous report where zVAD showed marked protection against SM-induced apoptosis in 16HBEo − -cells (Sourdeval et al, 2006) may be due to the use of a different cell lines or due to differences in study design. In our protocol cells were not pre-treated or co-incubated with the inhibitor during SM exposure to avoid direct interaction of SM with zVAD.…”
Section: Discussioncontrasting
confidence: 99%
“…Whether this oxidation is directly because of CEES, its metabolites, or the ROS that is formed is yet to be determined. The increased ROS we have seen in mitochondria may be because of mitochondrial dysfunctional, which we have seen in our CEES model and what others have seen after SM exposure (Sourdeval et al, 2006). The mitochondrion, specifically the respiratory chain, can produce a substantial amount of endogenous ROS (Fridovich, 1978;Drose and Brandt, 2008), and, if CEES causes mitochondrial uncoupling, this could explain oxidation products seen in other areas of the cell and markers of apoptosis (Dillman et al, 2005;Sourdeval et al, 2006).…”
Section: Discussionsupporting
confidence: 62%
“…Sourdeval et al indicated a mitochondrial pathway in the bronchial epithelial cell line, 16HBE, after an increase of p53, cytochrome c and the activation of caspase -2, -3, -8, -9 and -13 (Sourdeval et al, 2006). Also correlating with our results Ray et al demonstrated an activation of caspase 3 in undifferentiated normal human bronchial epithelial cells (Ray et al, 2008).…”
Section: Discussionsupporting
confidence: 91%